2011
DOI: 10.1016/j.eurpsy.2009.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Telepsychiatry and carer education for schizophrenia

Abstract: Telepsychiatry can deliver effective carer education programmes about schizophrenia and may provide one solution to bridging the chasm between scientific evidence and clinical reality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 22 publications
0
25
0
2
Order By: Relevance
“…59,60 Though preliminary, the early indications from the findings suggest that carers understanding about psychosis may benefit from the use of digital technologies and the approach might be acceptable (e.g. 45,48,50 ). Further exploration of the benefits of using different approaches to support carers in facilitating their knowledge and understanding about their relative's mental health condition, which also extend beyond traditional face-to-face meetings 61 would represent important research developments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…59,60 Though preliminary, the early indications from the findings suggest that carers understanding about psychosis may benefit from the use of digital technologies and the approach might be acceptable (e.g. 45,48,50 ). Further exploration of the benefits of using different approaches to support carers in facilitating their knowledge and understanding about their relative's mental health condition, which also extend beyond traditional face-to-face meetings 61 would represent important research developments.…”
Section: Discussionmentioning
confidence: 99%
“…48 Participants were predominately female in eight of the nine studies that provided gender data. 45,46,48,49,50,51,52,53 While more than half the studies employed carer only participants only, four papers reported data for carer participants and the individuals they provided informal care for. 45, 46,47, 53…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Audiology, the mainly themes approached are about public health, hearing diagnosis, intervention and rehabilitation, produced in different formats, which each one was adequated to its target public [34][35][36][37][38][39][40] . Nevertheless, there is difficultness, mainly financial in make available these materials to a large number of professionals, what turns the promotion and access restrict.…”
Section: Resultsmentioning
confidence: 99%